Low cost, high performance ultrafiltration membranes from glass fiber-PTFE–graphene composites - Coleman, Jonathan; Boland, Coilin (My University, 2020)
The development of low-cost ultrafiltration membranes with relatively high flow rate and selectivity is an important goal which could improve access to clean water in the developing world. Here we demonstrate a method to infuse mixtures of graphene nanosheets and Teflon nanoparticles into ultra-cheap glass fibre membranes. Annealing the resultant composites leads to coalescence of the Teflon, resulting in very stable membranes with significantly enhanced mechanical properties. In filtration tests, while adding ~ 10 wt% graphene/Teflon to the glass fibre membrane decreased the flow rate by × 100, the selectivity improved by × 103 compared to the neat glass fibre membrane. This combination of selectively and flow rate was significantly better than any commercial membrane tested under similar circumstances. We found these membranes could remove > 99.99% of 25–250 nm diameter SiC nanoparticles dispersed in ethanol, transmitting only particles with diameters < 40 nm, performance which is superior to commercial alumina membranes. Field trials on dirty canal water showed these composite membranes to remove aluminium to a level × 10 below the EU limit for drinking water and reduce iron and bacteria contents to below detectable levels.
Keywords: clean water; water-related illnesses; Water purification by filtration; clean water; water-related illnesses; Water purification by filtration